Pemanfaatan Grafologi sebagai Media Pengenalan Diri dan Peningkatan Kepercayaan Diri pada Mahasiswa Psikologi Universitas Sahid Surakarta - Emalia Yunika; Annieiz Rachmawati Musslifah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Basically everyone has self-confidence, but everyone's self-confidence is different. There are many people who are inferior to themselves and many who are confident, but they show different behaviors. Not everyone has confidence, and some people lack confidence. Graphology is based on the relationship with one's subconscious mind, while handwriting arises from the reflection of one's subconscious mind, so the two can be connected. Community service activities are carried out with a structured and gradual approach in order to achieve predetermined goals. The results achieved show a significant increase in student understanding which is characterized by increased self-confidence and previously unknown graphology knowledge. The advantage of this activity is the interactive speaker approach that stimulates active student participation. For further development, it is recommended to hold further training with a longer duration and focus on other knowledge with graphology, as it is considered important for the expansion of student knowledge.